The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.48550/arxiv.2201.09051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Robustness of Sparse Counterfactual Explanations to Adverse Perturbations

Abstract: Counterfactual explanations (CEs) are a powerful means for understanding how decisions made by algorithms can be changed.Researchers have proposed a number of desiderata that CEs should meet to be practically useful, such as requiring minimal effort to enact, or complying with causal models. We consider a further aspect to improve the usability of CEs: robustness to adverse perturbations, which may naturally happen due to unfortunate circumstances. Since CEs typically prescribe a sparse form of intervention (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In summary, feasible, actionable, and sparse counterfactual explanations recommend causality-consistent scenarios that can be reasonably implemented by the individuals impacted by algorithmically-generated outcomes, once they act on the values of a limited number of features. Finally, we note that authors have recently suggested additional desiderata of counterfactual explanations, such as diversity and robustness to local perturbations [10], [12], [17]. The former refers to the possibility of generating diverse counterfactuals for a given outcome to explain [10].…”
Section: B Selected Desiderata Of Counterfactual Explanationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In summary, feasible, actionable, and sparse counterfactual explanations recommend causality-consistent scenarios that can be reasonably implemented by the individuals impacted by algorithmically-generated outcomes, once they act on the values of a limited number of features. Finally, we note that authors have recently suggested additional desiderata of counterfactual explanations, such as diversity and robustness to local perturbations [10], [12], [17]. The former refers to the possibility of generating diverse counterfactuals for a given outcome to explain [10].…”
Section: B Selected Desiderata Of Counterfactual Explanationsmentioning
confidence: 99%
“…In fact, the goal of diversity is to provide individuals with different counterfactual scenarios to perform algorithmic recourse [10]. The latter refers to the degree to which counterfactuals are sensitive to (possibly adverse) perturbations of the data point whose machine learning outcome has to be explained, instead [12], [17]. We refer to [10], [12], [17] for all details.…”
Section: B Selected Desiderata Of Counterfactual Explanationsmentioning
confidence: 99%
See 2 more Smart Citations